The association of BRCA1 and BRCA2 mutations with prostate cancer risk, frequency, and mortality: A meta‐analysis. Issue 8 (22nd March 2019) - Oh, Mok; Alkhushaym, Nasser; Fallatah, Saad; Althagafi, Abdulhamid; Aljadeed, Rana; Alsowaida, Yazed; Jeter, Joanne; Martin, Jennifer R.; Babiker, Hani M.; McBride, Ali; Abraham, Ivo
Abstract: Background: A prior meta‐analysis found no association between BRCA1 mutation and prostate cancer (PCa). Subsequent BRCA2 mutation studies have shown an association with PCa risk and mortality. We conducted a meta‐analysis of overall BRCA mutation carriers and in subgroups to (1) estimate PCa risk in BRCA mutation carriers, (2) evaluate the frequency of BRCA mutation carriers in patients with PCa, and (3) compare cancer‐specific survival (CSS) and overall survival (OS) among BRCA mutation carriers and noncarriers. Methods: We searched the PubMed/MEDLINE, Embase, and Cochrane databases. Unadjusted odds ratio (OR), percentage (%), and hazard ratio (HR) were used to calculate pooled estimates for PCa risk, frequency, and survival, respectively. Subgroup analyses by mutation type ( BRCA1 or BRCA2 ) were conducted for the three objectives. Further subgroup analyses by study design (age‐sex‐adjusted or crude), ascertainment method (ascertained or inferred genotyping), population (Ashkenazi Jewish or general population), and survival outcomes (CSS or OS) were conducted. The associations were evaluated using random‐effects models, in two‐sided statistical tests. Results: A total of 8 cohort, 7 case‐control, 4 case‐series, 28 frequency, and 11 survival studies were included. Being a BRCA mutation carrier ( BRCA1 and/or BRCA2 ) was associated with a significant increase in PCa risk (OR = 1.90, 95% CI = 1.58‐2.29), with BRCA2 mutation being associated with a greater risk of PCa (OR = 2.64, 95% CI = 2.03‐3.47) than BRCA1 (OR = 1.35, 95% CI = 1.03‐1.76). The frequency of BRCA1 and BRCA2 carriers in patients with PCa was 0.9% and 2.2%, respectively. OS (HR = 2.21, 95% CI = 1.64‐2.30) and CSS (HR = 2.63, 95% CI = 2.00‐3.45) were significantly worse among BRCA2 carriers compared to noncarriers, whereas OS (HR = 0.47, 95% CI = 0.11‐1.99) and CSS (HR = 1.07, 95% CI = 0.38‐2.96) were statistically not significant when comparing BRCA1 carriers and noncarriers. Conclusions: There is a 1.90‐fold greater risk of PCa in overall BRCA mutation carriers. This elevated PCa risk is attributable mainly to a 2.64‐fold greater risk of PCa in BRCA2 carriers compared to a moderate 1.35‐fold greater risk in BRCA1 carriers. The frequency of BRCA2 mutations was higher than BRCA1 mutations among patients with PCa. BRCA2 but not BRCA1 mutations were associated with higher PCa mortality. The BRCA mutation may be a clinical factor to stratify high‐risk patients and guide clinical strategies for more effective treatments for patients with PCa.